Intra-peritoneal antibiotic utilization among Continuous Ambulatory Peritoneal Dialysis (CAPD) patients with peritonitis at a tertiary hospital setting in Malaysia - Ahmad, Mastura; Zin, Che Suraya; Ab Rahman, Ab Fatah (2019)
Introduction: Patients using CAPD are commonly associated with peritonitis. Peritonitis is a significant cause of morbidity, mortality and permanent transfer to haemodialysis in these patients. However, little is known about the utilization of antibiotic for the treatment of peritonitis in patients using CAPD. Objectives: This study aimed to evaluate the patterns of intra-peritoneal antibiotics utilization for the treatment of peritonitis in CAPD patients. Materials and Methods: This was a retrospective study conducted at a tertiary hospital setting in Malaysia. Medical records of CAPD patients who were diagnosed with peritonitis and registered with National Kidney Registry during 2013 to 2018 were reviewed. Types of antibiotics used and its dose and duration were recorded and reported using the ATC/DDD system. Results: A total of 105 peritonitis episodes were recorded from 72 patients. The most common first line empiric combinations used were ceftazidime/cefazolin (42%, n=), followed by cefepime/cefazolin (32%,n=) and ceftazidime/cloxacillin (27%, n=).